Protective factors as mediators between trauma and internalizing difficulties among male and female young adults - Jenkins, Lyndsay N. (Violence and victims, 2024)
The goal of this study was to examine the indirect effect of protective factors (i.e., resilience, coping, and self-esteem) on the association between exposure to traumatic events in childhood and internalizing difficulties for men and women. We surveyed 583 young adults aged 18 to 25 years about past exposure to traumatic events and current internalizing difficulties. The results suggest that there is a significant indirect effect of protective factors on the association between lifetime traumatic event exposure and internalizing distress. Furthermore, there was a gender difference between groups for the indirect effect of protective factors; protective factors had a mediating effect for women but not for men. This study highlights the importance of protective factors in understanding why some individuals experience internalizing difficulties after exposure to traumatic events. When working with victims of traumatic events, it is essential to consider their sex and the presence of protective factors such as coping, resilience, and self-esteem.